Effective interfacial tension effect on the instability of streaming rivlin-ericksen elastico-viscous fluid flow through a porous medium - Singh, Mahinder (Zielona Góra: Uniwersytet Zielonogórski)
The instability of the plane interface between two uniform, superposed and streaming Rivlin-Ericksen elastico-viscous fluids through porous media, including the "effective interfacial tension" effect, is considered. In the absence of the "effective interfacial tension" stability/instability of the system as well as perturbations transverse to the direction of streaming are found to be unaffected by the presence of streaming if perturbations in the direction of streaming are ignored, whereas for perturbation in all other directions, there exists instability for a certain wave number range. The "effective interfacial tension" is able to suppress this Kelvin-Helmholtz instability for small wavelength perturbations, the medium porosity reduces the stability range given in terms of a difference in streaming velocities.
Keywords: Kelvin-Helmholtz instability; Rivlin-Ericksen elastico-viscous fluids in porous medium